Questions to the PM versus questions by the PM: an examination of the state and nature of 'Punch and Judy' politics during PMQs at Westminster. Issue 1 (2nd January 2020) - Shephard, Mark; Braby, Daniel
ABSTRACT: We know about what the public thinks of PMQs, and we know an increasing amount about questions to PMs. However, very little is known about the nature and state of questions that the PM asks during the procedure. Controlling for the average length of PMQs, we find that while the average number of Order Paper questions reached has stayed relatively static, the total number of questions asked has nearly halved over time while questions asked by the PM (including questions levelled at both the Leader of the Opposition and the opposition) have increased over time. We also find that specific blaming by the PM of the previous government is far higher right after party rotation in government (Blair and Cameron) than after PM rotation intra-party government (Brown and May). Finally, we find that Cameron was significantly more likely to ask questions during PMQs when this correlated with higher public opinion net approval ratings.